RELATIONSHIP LEADERSHIP QUALITY AND CULTURE ORGANIZATION WITH THE PERFORMANCE OF SMAN 28 TANGERANG DISTRICT - Putra, Anggih Perian Guswan (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2019)
This research was conducted to determine the relationship between the quality of the Principal's leadership and organizational culture with the performance of SMAN 28 Tangerang District employees. The study uses a quantitative approach with a descriptive correlational survey method, using correlation theory which is about product moment. Research data collection techniques from respondents carried out through questionnaires or questionnaires. The sample population was 103 employees in each section of SMAN 28 Tangerang, with simple random sampling technique. The magnitude of the effect of leadership quality and organizational culture together on employee performance by 87.2% This shows the higher the quality of leadership and organizational culture, the better the performance of employees, and vice versa the lower the quality of leadership and organizational culture will have an impact for employee performance.